Improving Teachers Professionalism to Face the Global Education Challenges: The Context of Brunei Darussalam - Noor, Abdullah Mohd; Hamidon, Zahari (SOSIOHUMANIKA, 2010)
ABSTRACT: This paper discusses characteristics of a profession, ingredients of professionalism, reviews on teachers and teaching profession, role of a teacher, the continuing questions of professionalism, and improving teacher professionalism. For Brunei Darussalam, Master of Teaching (M-Teach) and role of ICT (Information and Communication Technology) in teacher education programmes are highlighted in the current academic session. In coming semester, the Malay medium M-Teach in SHBIE (Sultan Hassanal Bolkiah Institute of Education) will be introduced to cater for multiculturalism in Brunei Darussalam. A part from that Arabic medium of instruction will be also included in SHBIE, UBD (University of Brunei Darussalam) and Kolej Universiti Perguruan Agama Seri Begawan (Religious Teachers University College Seri Begawan) programme. In line with the 21st century skills, teachers training should consider in integrating current global issues such as new technology, diverse cultures, religions, languages and lifestyles in a spirit of mutual respect, and open dialogue in personal, work, and community contexts. Pedagogical consideration should also include by providing opportunities for âactive learningâ and humour to encourage pupil engagement, making learning interesting, and explaining things clearly.Key words: teacher professionalism, Master of Teaching, role of ICT, and challenge for the National Education System for 21st Century in Brunei Darussalam.Â Â About the Authors: Dr. Abdullah Mohd Noor is a Senior Lecturer at the Sultan Hassanal Bolkiah Institute of Education UBD (University of Brunei Darussalam); and Dr. Zahari Hamidon is also Senior Lecturer at the Department of Educational Foundation SHBIE UBD, Jalan Tungku Link, BE1410 Gadong, Negara Brunei Darussalam. They can be reached at: abdullahmohdnoor@yahoo.com and zaharimy@hotmail.comHow to cite this article? Noor, Abdullah Mohd & Zahari Hamidon. (2010). âImproving Teachers Professionalism to Face the Global Education Challenges: The Context of Brunei Darussalamâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.3, No.1 [Mei], pp.1-22. Bandung, Indonesia: Minda Masagi Press, UNIPA Surabaya, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (February 11, 2010); Revised (March 14, 2010); and Published (May 20, 2010). Â Â